Deoxyribonucleic Acid (DNA) Computing using Two-by-Six Complementary and Color Code Cipher - B Adithya; G Santhi (Indonesian Scientific Journal, 2021)
Information obnubilating hides information to obviate the information from being leaked into the subsisting networking in order to see the exact confidentiality of all their germane info, which plays a paramount part in Deoxyribonucleic Acid (DNA) cryptography. In this paper, DNA computing color code cryptographic strategy is proposed to ensure that the data protection out of the eavesdropper. The text message in format is encrypted into cipher shade utilizing DNA cryptography. There is a supersession procedure utilized to obnubilate the mystery message that was scrambled to some reference DNA. That is the bases of the benchmark DNA are superseded together with the generic DNA depending on a standard two-by-six complementary pair rule. Representation of text gives a color of universal and thus a little substantial difference in coloring is more complicated to understand than changes in brightness.